PENGEMBANGAN KAWASAN AGRIBISNIS JAGUNG DAN MANGGA DI KABUPATEN BLORA - Ernoiz Antriyandarti; Susi Wuri Ani (University of Jember, 2017)
Blora is one of the main producers of corn and mango in Central Java which have highcontribution to the national production. Therefore, Agribusiness Region Development of cornand mango in Blora is very important to stimulate economy growth based on regional potencyinvolved by all actors of agribusiness such as government, farmer, and private sector in Blora.The objective of this research is to determine comparative advantage of corn and mango in Blora and to formulate how to develop those commodities. This study applied farming analysis and Policy Analysis Matrix (PAM). The result of the study show that agribusiness of corn and mangoare profitable and there are not any diseconomies resulted from those agribusiness activites.Therefore, agribusiness of those commodities can be developed further.